2017
DOI: 10.1109/tasc.2016.2628814
|View full text |Cite
|
Sign up to set email alerts
|

Design and R&D for the DEMO Toroidal Field Coils Based on Nb3Sn React and Wind Method

Abstract: In 2013, the Swiss Plasma Center (SPC) proposed a Toroidal Field (TF) layout for the DEMO-EUROfusion tokamak, based on a graded winding made of layers of Nb 3 Sn (react&wind) and NbTi conductors. The R&D effort led in 2015 to a full size prototype conductor tested up to 82.4 kA at 12.35 T. The test continued in 2016 and new results are presented. In summer 2015 a new reference baseline was issued for the DEMO-EUROfusion tokamak, leading to an update of the TF requirements. The design update is presented in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Out of these three alternative conductor designs, one option (TF WP#1) [71,72] is based on the react & wind (R&W) method for Nb 3 Sn magnets, in which the rectangular conductor is wound after the heat treatment, which is carried out without the stainless steel (SS) conduit and electrical insulation. The main advantage of this approach is the reduction of the effective strain acting on the superconducting cable, with an improvement of the transport capability of the superconducting strands.…”
Section: Superconducting Magnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these three alternative conductor designs, one option (TF WP#1) [71,72] is based on the react & wind (R&W) method for Nb 3 Sn magnets, in which the rectangular conductor is wound after the heat treatment, which is carried out without the stainless steel (SS) conduit and electrical insulation. The main advantage of this approach is the reduction of the effective strain acting on the superconducting cable, with an improvement of the transport capability of the superconducting strands.…”
Section: Superconducting Magnetsmentioning
confidence: 99%
“…The WP is wound in single layers (SL) which allows the grading of both superconductor (SC) and SS cross-sections in the different layers, with a relevant saving on costs. The results of the first experimental campaigns [71,72] helped to improve the layout of the conductor. Tests carried out on the last design [73] have demonstrated that there is no degradation of the current sharing temperature (Tcs) of the conductor after 1000 electro-magnetic (e-m) cycles and 4 thermal cycles.…”
Section: Superconducting Magnetsmentioning
confidence: 99%
“…WP#1 [6,7] is based on the R&W method for Nb 3 Sn magnets, in which the conductor is wound after the heat treatment, which is carried out without the stainless steel (SS) conduit and electrical insulation. The WP is wound in single layers (SL); this approach allows the grading of both superconductor (SC) and SS cross-sections in the different layers, depending on the magnetic field and the local stress value, respectively.…”
Section: Tf Wp#1 Designmentioning
confidence: 99%
“…Results after the WUCD of the 2016 experimental campaign for RW1 sample are reported in Fig. 3 [6]. The "effective strain", ε eff , is the parameter to be used in the strand scaling law to fit the conductor performance.…”
Section: Tf Wp#1 Designmentioning
confidence: 99%
“…The conductors are composed of a flat cable with low void fraction which is reacted before jacketing; therefore the thermal compression exerted by the steel jacket on the Nb 3 Sn cable acts only from room temperature to 4.2 K, instead of starting close to the reaction temperature. The high field conductors were manufactured industrially and the effective strain fitting parameter was estimated between -0.28% and -0.32% in SPC-RW1 [26] (in this sample the jacket was only 3 mm thick). Recently [27] a second prototype, SPC-RW2, designed for different operating conditions, has been manufactured and tested; the effective strain fitting parameter shifted from an initial value of -0.35% to -0.40% after 1000 cycles.…”
Section: Review Of Demo Prototype Conductorsmentioning
confidence: 99%